Optimalisasi Partisipasi Peserta Program Pengelolaan Penyakit Kronis (Prolanis) melalui Edukasi Kesehatan Berbasis Komunitas di Wilayah Kerja UPTD BLUD Puskesmas Batunyala - Hapipul Fahri; Rahmania Ambarika (Yayasan Inspirasi El Burhani, 2026)
Introduction: Low participation in the Chronic Disease Management Program (Program Pengelolaan Penyakit Kronis/Prolanis) remains a challenge in primary healthcare services, particularly among patients with hypertension and type 2 diabetes mellitus. Preliminary assessment conducted during the residency program at UPTD BLUD Batunyala Public Health Center identified limited knowledge regarding Prolanis, inadequate dissemination of information, and suboptimal community engagement as the main factors contributing to low attendance in Prolanis activities. These findings became the basis for implementing a community-based health education program to improve participants' understanding and encourage active participation. Objective: The purpose of this service was to optimize community participation in the Prolanis program through community-based health education among patients with hypertension and type 2 diabetes mellitus in the working area of UPTD BLUD Batunyala Public Health Center. Method: This public service was conducted by implementing community-based health education using an educational and participatory approach. Activities included interactive lectures, group discussions, question-and-answer sessions, and the distribution of educational leaflets and posters. The program targeted patients diagnosed with hypertension and type 2 diabetes mellitus and was carried out collaboratively with healthcare professionals and community health volunteers. Result: A total of 21 participants completed the community service program. Before the educational intervention, 17 participants (81.0%) demonstrated inadequate knowledge of the Prolanis program, while only 4 participants (19.0%) had adequate knowledge. Following the community-based health education intervention, all participants (21 participants, 100%) demonstrated adequate understanding of the Prolanis program, hypertension, type 2 diabetes mellitus, and the importance of regular participation in Prolanis activities. Participants also showed greater enthusiasm during the educational sessions, actively engaged in discussions, and expressed increased motivation to participate in future Prolanis activities. The use of visual educational media (leaflets and posters) facilitated participants' comprehension and supported more effective health promotion. Conclusion: Community-based health education is an effective strategy to improve knowledge and promote community participation in the Prolanis program. Strengthening health education using participatory methods and visual educational media may enhance community engagement and support the sustainability of chronic disease management programs in primary healthcare settings